Experience with chondroitin sulfate in the combination therapy of lower back pain - O. A. Shavlovskaya; I. D. Romanov; Yu. S. Prokofyeva (Неврология, нейропсихиатрия, психосоматика, 2020)
Standard treatment for lower back pain (LBP) includes the use of nonsteroidal anti-inflammatory drugs (NSAIDs).Objective: to determine the magnitude of the effect of injectable chondroitin sulfate (CS) as part of combination therapy for LBP on the intensity of pain syndrome.Patients and methods. The investigation was conducted in August 2019 to February 2020. A total of 60 patients (23 men and 37 women) aged 36 to 66 years (mean age, 48.65±8.72 years) with non-specific LBP were followed up. The patients were divided into two equal groups. A study group (n=30) took a NSAID (meloxicam) 7.5 mg twice daily for 7—10 days and intramuscular (i.m.) CS every other day in accordance with the scheme: the first three injections at a dose of 1 ml (100 mg) on days 1, 3, and 5; if this was well tolerable, a dose of 2 ml (200 mg) from the 4th injection (on day 7). A control group (n=30) used meloxicam 7.5 mg twice daily for 7—10 days. Changes in the patients' status were evaluated at baseline and 10, 20, and 50 days after therapy. The authors used a numerical rating scale (NRS) to determine the intensity of pain (at rest, during walking, during palpation), as well as the Oswestry functional status scale (OFSS). Adverse events (AEs) were evaluated.Results and discussion. In the study group, there was a decreased need for NSAIDs on day 7 of therapy, whereas in the control group, there were no dosage regimen changes through the treatment cycle. The intensity of pain syndrome according to the NRS decreased by 89.8% in the study group and by 68.3% in the control group; that according to OFSS reduced by 95.5% in the study group and by 86.6% in the control group (p<0.05). The use of i.m. CS injections in the combination therapy of LBP increases the efficiency of treatment, can reduce the dose of NSAIDs and improve the functional capabilities of the patients with pain syndrome. The safety of CS was confirmed by the absence of AEs throughout the follow-up period.Conclusion. The investigation has demonstrated that the use of i.m. CS injections in the combination therapy of LBP can improve treatment outcomes.